2007
DOI: 10.1152/jn.00572.2007
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Space Analysis Suggests Multi-Site Plasticity Contributes to Motor Pattern Initiation inTritonia

Abstract: This research examines the mechanisms that initiate rhythmic activity in the episodic central pattern generator (CPG) underlying escape swimming in the gastropod mollusk Tritonia diomedea. Activation of the network is triggered by extrinsic excitatory input but also accompanied by intrinsic neuromodulation and the recruitment of additional excitation into the circuit. To examine how these factors influence circuit activation, a detailed simulation of the unmodulated CPG network was constructed from an extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 48 publications
0
44
0
Order By: Relevance
“…Cutting this commissure or blocking action potential propagation along it also prevented the production of the fictive motor pattern in isolated brain preparations. This functional impairment is at least partly attributable to the loss of excitation from C2 to VSI in the pedal ganglion distal to the lesion; modeling studies showed that this C2-evoked VSI excitation is critical for the motor pattern generation (Calin-Jageman et al, 2007). Both the behavior and the fictive motor pattern recovered within 20 h of creating the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutting this commissure or blocking action potential propagation along it also prevented the production of the fictive motor pattern in isolated brain preparations. This functional impairment is at least partly attributable to the loss of excitation from C2 to VSI in the pedal ganglion distal to the lesion; modeling studies showed that this C2-evoked VSI excitation is critical for the motor pattern generation (Calin-Jageman et al, 2007). Both the behavior and the fictive motor pattern recovered within 20 h of creating the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…7C). In contrast, the synaptic potentials reported in the later experiments by Calin-Jageman et al (2007) were made with the commissure intact. Thus, the researchers may have been examining different states of the same circuit.…”
mentioning
confidence: 87%
“…Differences in the thresholds of elements in these pathways produce responses characteristic of a particular status. However, relative differences in other parameters of the pathways, such as synaptic efficacy or input resistance of the neurons, could produce similar effects, leading to the conclusion that the status-dependent effects appear to result from differences in the relative excitabilities of circuit pathways that produce ipsilateral excitation, bilateral excitation, and bilateral inhibition (Calin-Jageman et al, 2007;Issa et al, 2011;Koch et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…When fitting new timeseries, instead of re-estimating the parameters for a dynamic regime that might have been inferred before, a dictionary search is conducted, and observed dynamics are related to probable parameter settings. The idea of generating simulation databases was previously successfully applied to several neuroscience models (Calin-Jageman et al, 2007;Doloc-Mihu and Calabrese, 2011;Gü nay et al, 2008Gü nay et al, , 2009Gü nay and Prinz, 2010;Lytton and Omurtag, 2007;Prinz et al, 2003).…”
mentioning
confidence: 99%